Some basic vowel features, their articulatory correlates and their explanatory power in phonology - Fischer-Jørgensen, Eli (Annual Report of the Institute of Phonetics University of Copenhagen, 1984)
The classical articulatory vowel features, vowel height (or degree of openness) and front-back, have been criticized as physiologically inexact and in reality based on a misinterpretation of auditory impressions. Some want to replace them by new features, partly based on constriction (Wood), others want to interpret them exclusively in auditory terms (Ladefoged). It is argued in this paper that the classical articulatory vowel features are not as inexact physiologically as maintained by their critics, and that they are indispensable in phonological descriptions and in this respect more useful than e.g. Wood’s feature system.